Multi-target mechanisms and potential applications of quercetin in the treatment of acne vulgaris - Bo, Yang; Li, Yiming (Frontiers in Pharmacology, 2025)
Acne vulgaris, a prevalent inflammatory dermatosis, afflicts approximately 90% of adolescents globally. Despite the efficacy of conventional therapies, including antibiotics and retinoids, their use is frequently limited by adverse effects and the emergence of drug resistance. Quercetin, a naturally occurring flavonoid, has garnered significant attention owing to its diverse biological activities, encompassing anti-inflammatory, antioxidant, antimicrobial, and immunomodulatory properties. This review comprehensively explores the multi-target mechanisms of quercetin in the treatment of acne, focusing on its ability to modulate inflammatory cytokine production, oxidative stress pathways, sebaceous gland activity, and microbial populations. Additionally, quercetin promotes skin barrier repair and reduces post-inflammatory hyperpigmentation and scarring through its antioxidant and anti-fibrotic effects. Despite promising in vitro and preclinical findings, challenges such as quercetin’s low bioavailability and lack of robust clinical evidence necessitate further research. Advanced delivery systems, including nanoparticles and combination therapies, may optimize its therapeutic potential. This review provides insights into the molecular mechanisms and clinical applications of quercetin, highlighting its potential as a safe and effective alternative for acne management.